Inserção profissional de jovens aprendizes em Santana do Livramento/RS - (:unkn) unknown (Universidade Federal do Pampa, 2025)
The present study aimed to analyze the perception of young apprentices from Santana do Livramento regarding their experience in the Young Apprentice Program as an effective tool for professional integration. To this end, a qualitative and descriptive approach was adopted, using the thematic oral history method to investigate the experiences and perceptions of the participants. Data collection was carried out through semi-structured interviews with seven young apprentices, intentionally selected to cover different trajectories related to their formal job market placement, sectors of activity, and length of time in the program. The results demonstrate that all interviewees recognize the importance of the program for their insertion in the formal job market, highlighting the development of technical and behavioral skills, in addition to the importance of the theoretical course offered. Although some participants were hired or obtained new professional opportunities, others opted for alternative trajectories, such as entrepreneurship or rural work. In addition, the program contributed significantly to the personal and professional development of the young people. On the other hand, the need for stricter monitoring of companies was also highlighted, in order to promote good qualifications and fair working conditions. In this way, the Young Apprentice Program is an important instrument of social and professional inclusion for young people in the region analyzed.
Professional integration of young apprentices in Santana do Livramento/RS
Keywords: Jovem aprendiz; Inserção profissional; Trajetória profissional; Mercado de trabalho; Inclusão social; Young apprentice; Professional insertion; Professional trajectory; Labor market; Social inclusion; CIENCIAS SOCIAIS APLICADAS